Peningkatan Kompetensi Guru Untuk Pembelajaran Interaktif Melalui Pelatihan Pembelajaran Metode Contextual Teaching and Learning (CTL) - Suherman; Yani, Achmad; Rusdi, Muhammad; Suprianto (Jurnal Ilmiah Madiya (Masyarakat Mandiri Berkarya), 2024)
The Community Partnership Service Program (PKM) is implemented at MIS Putri Babussalam with the general aim of overcoming partner problems. Meanwhile, the specific objective of this PKM program is to provide multimedia-based contextual teaching and learning (CTL) method training for MIS Putri Babussalam teachers. There were 9 teachers who participated in the training, and all of them were Bachelor's Degree graduates from various disciplines, but they are still weak in carrying out active CTL learning. The PKM TEAM also provided assistance with an LCD projector and projector screen, as well as training on their use and utilization for the learning process. The method used in this PKM program is in the form of collecting data about potential partners through surveys and interviews with madrasah principals. Then, from the data, a community service program is made, and implementation and program evaluation are carried out. The activity was carried out for 3 months. Starting from the preparation stage in the form of surveys and interviews with partners, then the implementation of multimedia-based contextual teaching and learning (CTL) training for teachers and the use of LCD projectors to support CTL learning. When the evaluation was carried out, it was found that the teachers were active in compiling CTL learning plans, namely making PowerPoint programs and putting videos and photos related to the material through hyperlinks. Then the teachers had carried out active CTL learning using multimedia in turns because the existing LCD projectors were still available. limited. Thus, these results indicate the achievement of PKM objectives as expected.